Presentation of the Multidimensional Couple: Socioemotional Impact Scale - Medina Centeno, Raúl; Méndez-Espina, Sara; Llosa, José Antonio; Agulló-Tomás, Esteban (Interacciones, 2024)
Introduction: A systemic instrument is presented to measure the socioemotional network in relation to the partner and the person's perception of the impact of this intimate network on his or her partner for his or her classification. It is based on the idea that a nurtured social network brings positive benefits to one's nuclear partner. In order to verify this assumption both in research and in clinical practice, it is necessary to construct a complex instrument that allows reaching different dimensions within and outside the couple. Objective: The study seeks the construction and validation of the Multidimensional Couple scale to measure seven dimensions in the couple: emotional, cognitive, physical interest, protection, trust, respect and power, as well as an additional dimension to classify the type of couple. Method: An Exploratory Factor Analysis (EFA) and Exploratory Factor Analysis (CFA) were carried out to test the psychometric properties and the adequacy to the theoretical model. A total of 1149 people (71.5% women and 28% men) living in Mexico participated. Result: The presence of a scale formed by 7 dimensions in the couple and a second order factor is confirmed, which can be applied both by adjusting the answers to the couple itself and to other people different from the couple. The goodness-of-fit and reliability indices are satisfactory. Conclusion: This scale provides a psychometric instrument that allows the study of the relationship between the couple.